433 SAME SPECIALITY, DIFFERENT REALITY?. (14th June 2021) - Gomez, A; Capon-Saez, A; Gomez-Mosquera, A; Parada-DeFreitas, Y; Arechaderra-Calderon, J J; Hoyos, E; Jackson, H; Ramon-Espinoza, F; Vilches-Moraga, A
Abstract: Introduction: The United Kingdom and Spain run government-funded social and health care services, free for the user at the point of delivery. Acute Geriatric Units (AGU) carrying out Comprehensive Geriatric Assessments improve the clinical outcomes of older patients. Little is known about the similarities and differences between countries, and how these may impact on clinical outcomes. Methods: Prospective observational study of consecutive patients admitted to AGU of 2 hospitals in the UK and 4 hospitals in Spain between the 1st to the 30th of October 2019 and from the 1st to the 29th of February 2020. We followed up the patients for a 90 day period. Conclusions: Frailty, multimorbidity and polypharmacy were prevalent in both cohorts. English patients were younger, with shorter hospital stay, mortality and use of antipsychotic medication but higher readmission rates. Involvement from Allied health care professionals was higher in UK hospitals.